Simultaneous Extraction, Enrichment and Removal of Dyes from Aqueous Solutions Using a Magnetic Aqueous Micellar Two-Phase System - Shuanggen Wu; Danyu Sun; Chaoyun Wang; Yuanru Yang; Fenfang Li; Zhijian Tan (Applied Sciences, 2017)
The magnetic aqueous micellar two-phase system (MAMTPS) has the advantages combined of magnetic solid phase extraction (MSPE) and aqueous micellar two-phase system (AMTPS). Thus, MAMTPS based on Fe3O4 magnetic nanoparticles (MNPs) and a nonionic surfactant Triton X-114 (TX-114) was developed for the extraction, enrichment and removal of three dyes (Congo red, methyl blue, and methyl violet) from aqueous solutions in this study. The MNPs Fe3O4@NH2 was screened as the optimal MNPs benefiting the extraction. Then, the influencing factors of MNPs amount, TX-114 concentration, vibration time, and extraction temperature were investigated in detail. The results showed that the extraction efficiencies of three dyes almost reached 100% using MAMTPS under the optimal conditions; MAMTPS had higher extraction ability than the individual MSPE or AMTPS. Thus, MAMTPS had the advantages of simple operation, high extraction ability, easy recycling of MNPs, and short phase-separation time, which showspotential for use in the extraction and analysis of contaminants from water samples.